2022
DOI: 10.20473/bikk.v34.2.2022.109-113
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Disability in Leprosy Patients: A Retrospective Study

Abstract: Background: Leprosy is a chronic granulomatous infectious disease caused by Mycobacterium leprae that affects peripheral nerves and skin. The interaction between M. leprae and Schwann cells causes irreversible damage to peripheral nervous tissue afterward disability occurs. Involvement of the major nervous trunks of the extremities can produce sensory-motor deficits. The risk factors are delay in diagnosis, gender, age, type of leprosy, duration of disease, number of affected nerves, leprosy reaction, type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…This belief coupled with the belief that Leprosy cannot be transmitted makes it difficult for people to appreciate the importance of contact tracing. It has been established that though the causative organism for Leprosy is Mycobacterium leprae , the mode of transmission is unknown (2,34). Contrary to this, there was no mention of Leprosy being a bacterial infection among the community members and the PAL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This belief coupled with the belief that Leprosy cannot be transmitted makes it difficult for people to appreciate the importance of contact tracing. It has been established that though the causative organism for Leprosy is Mycobacterium leprae , the mode of transmission is unknown (2,34). Contrary to this, there was no mention of Leprosy being a bacterial infection among the community members and the PAL.…”
Section: Discussionmentioning
confidence: 99%
“…Leprosy, also known as Hansen's disease, is one of the oldest recorded diseases. It is an infectious disease caused by the bacteria, Mycobacterium leprae (1)(2)(3). The bacterium has a lengthy incubation period of up to 20 years (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with research conducted by Widya 13 et al in 2017 in Pemalang Regency, which showed that the most patients were those who did not have a disability or a level 0 of 104 patients (72.2%), while 40 (27.8%) were those who had disabilities. Based on patients who experience disabilities (disability levels 1 and 2), a study conducted by Geani 14,15 et al in the Department of Dermatology and Venereology at the Dr. Soetomo Surabaya in 2017-2019 showed that in the span of 3 years, more new leprosy patients had grade 2 disability than grade 1, namely 88 patients (32%) had grade 2 disability and 64 patients (23.3%) had grade 1 disability. In this study, the number of new patients was relatively constant over a span of 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…23 The risk factors for disability in leprosy include the type of leprosy, disease duration, total affected trunks nervous, leprosy reaction, and neuritis. 24 Healthcare must give education regarding complications and disabilities that can occur.…”
Section: Discussionmentioning
confidence: 99%